Investigation of Factors Facilitating the Happiness of Individuals Participating in Leisure Activities - Veli Ozan Çakır (Journal of Educational Issues, 2024)
This study aimed to examine the factors that facilitate happiness in leisure. The research was performed according to the relational screening design, one of the scanning models. A total of 260 students, 180 male and 80 female, selected by simple random sampling method, studying at Istanbul University-Cerrahpaşa Faculty of Sport Sciences participated in the research group. In addition to the personal information form to collect data in the study, the Oxford Happiness Scale-Short Form (OHS-S) developed by Hills and Argyle (2002) and adapted into Turkish by Doğan and Çötok (2011), and the Leisure Facilitators Scale (LFS) developed by Kim et al. (2011) and adapted into Turkish by Gurbuz et al. (2015) were used as data collection tools. Considering the skewness and kurtosis values of the research data, it was accepted that the data showed a normal distribution. Moreover, t-test, ANOVA and Pearson Correlation test were used in the analysis. In this context, while no significant difference was found between the happiness of individuals according to their gender, a significant difference was determined between leisure facilitators. Moreover, a moderately significant relationship was found between leisure facilitators and happiness. As a result, personal, interpersonal and structural facilitators were identified as factors that facilitate the happiness of individuals in their leisure.